2016
DOI: 10.1007/s10827-016-0605-9
|View full text |Cite
|
Sign up to set email alerts
|

Automated evolutionary optimization of ion channel conductances and kinetics in models of young and aged rhesus monkey pyramidal neurons

Abstract: Conductance-based compartment modeling requires tuning of many parameters to fit the neuron model to target electrophysiological data. Automated parameter optimization via evolutionary algorithms (EAs) is a common approach to accomplish this task, using error functions to quantify differences between model and target. We present a three-stage EA optimization protocol for tuning ion channel conductances and kinetics in a generic neuron model with minimal manual intervention. We use the technique of Latin hyperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 64 publications
1
57
0
Order By: Relevance
“…Recent compartmental models of pyramidal neurons in L3 of the prefrontal cortex of rhesus monkeys suggested that aged animals have smaller C m values (~0.7 µF/cm 2 ) than young animals (~1.1 µF/cm 2 ) (Rumbell et al, 2016). Further direct measurements of C m , e.g., using the nucleated patch technique in different animals, could provide insights to the evolution of the specific capacitance of neuronal membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent compartmental models of pyramidal neurons in L3 of the prefrontal cortex of rhesus monkeys suggested that aged animals have smaller C m values (~0.7 µF/cm 2 ) than young animals (~1.1 µF/cm 2 ) (Rumbell et al, 2016). Further direct measurements of C m , e.g., using the nucleated patch technique in different animals, could provide insights to the evolution of the specific capacitance of neuronal membranes.…”
Section: Discussionmentioning
confidence: 99%
“…This network-level study represents an extension of our past modeling studies at the single-neuron level on parameters affecting firing properties of individual pyramidal neurons with aging (Coskren et al, 2015;Luebke et al, 2015;Rumbell et al, 2016), in different cortical regions , and in neurodegeneration (Goodliffe et al, 2018). The elegance of these network models lies in their ability to represent empirically observed changes in FR and synaptic weights with aging as perturbations to a small number of network parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted two general types of parameter exploration studies for the simulated DRT. The first were sweeps across parameter space using a space-filling Latin Hypercube Sampling (LHS) design, as in (Johnson et al, 1990;Rumbell et al, 2016). The LHS design identified 4200 points (networks) across the parameter space of synaptic weights (G EEa , G EEn , G IE , G EIa , G EIn , and G II ), representing semi-random combinations of the synaptic weights homogeneously distributed across the 6-dimensional space (Rumbell et al, 2016) (see Table 2).…”
Section: Exploring the Drt Model Parameter Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Within the field of computational neuroscience, evolutionary algorithms have been predominantly applied to the tuning of single-cell models or small groups of neurons [24, 25]. Here, we use them for automated tuning of biological reinforcement learning metaparameters in large-scale spiking networks with behavioral outputs.…”
Section: Introductionmentioning
confidence: 99%